Study on the construction method for in-situ expansion of existing large cross-section tunnels - Han Dayong; Zhong Xingwu; Liu Lei; Cui Hao; Li Dong; Yan Zihai; Chen Xiaojie; Yan Jiajia (Discover Applied Sciences)
Abstract This paper takes the in-situ expansion project of the Dachangshan tunnel as a case study to compare and optimize the construction method for the in-situ expansion of existing large cross-section tunnels. The deformation of the tunnel, the stress distribution of the surrounding rock, and the force on the tunnel support under three different construction schemes are examined in the paper. The results indicate that the “from top to bottom” construction scheme is superior to the “from left to right” scheme in terms of managing deformation and minimizing the demolition risk of the existing secondary lining. Moreover, the “from sidewall to inverted arch” construction scheme is more effective in controlling the deformation of the surrounding rock and reducing the stress on the initial support of the new tunnel. In particular, the risk of the secondary lining demolition has been evaluated, and it was reduced by adding steel pipe brace support. Finally, the field monitoring results verify the accuracy of the numerical calculation results and the safety of the optimal construction scheme.